Properties of abundance gradient along the Galactic disk and the role of LAMOST. Issue Volume 9:Issue S298(2013) (6th January 2014) - Hou, J.L.; Chen, L.; Yu, J.C.; Sellwood, J.; Pryor, C.
Abstract: In this paper, we present our recent work on the evolution of abundance gradients along the Milky Way disk based on the Geneva Copenhagen Survey (GCS) and Radial Velocity Experiment (RAVE) data. We will also discuss the role of the LAMOST Milky Way disk survey in clarifying the properties of metallicity breaks observed through open clusters and young tracers along the Milky Way disk. It is believed that the Galactic disk forms inside-out, in which the stellar population at increasing radii is younger and more metal poor. This picture is consistent with most Galactic Chemical Evolution (GCE) models which also predict a tight correlation between the metallicity and age of stars at a given radius. However, it is only a result of "steady state" and no dynamical evolution effects were taken into account. We have selected two stellar samples from GCS and RAVE, each sample contains about 10, 000 local thin-disk, main-sequence stars. We use the guiding radius which is determined by the conservation of z-direction angular momentum, to eliminate the blurring effects. And also use the effective temperature of the main sequence stars as a proxy of stellar age. It is shown that the metallicity gradient flattens as the age increases. This is not consistent with our previous GCE prediction, but can be explained by radial mixing effects. In order to further demonstrate the abundance breaks observed in the Galactic disk we have proposed, and have been carrying out, an open cluster survey project based on LAMOST. We plan to observe at least 400 open clusters in the northern Galactic sky. From the observations, we will get uniform parameters for those clusters with radial velocity and metallicities. We anticipate that this uniform open cluster sample could clarify the observed abundance break around the Milky Way disk corotation radius and also give a more robust result concerning the evolution of the abundance gradient.